Self-Raman Nd-doped vanadate laser: a pump source of organic crystal based difference frequency generation. Issue 10 (6th June 2020) - Liu, Pengxiang; Qi, Feng; Li, Weifan; Liu, Zhaoyang; Wang, Yelong; Ding, Xin; Yao, Jianquan
Abstract : We analyse a method of high repetition rate, efficient terahertz wave difference frequency generation (DFG) by using a self-Raman Nd-doped vanadate laser to pump 4'-dimethylamino-N-methyl-4-stilbazolium tosylate (DAST). A semi-analytical model is introduced that combines the rate equations (for the self-Raman dual-wavelength laser) and the coupled-wave equations (for the DAST-based DFG). Calculations were performed on a diffusion-bonded Nd:YVO4 -YVO4 laser with an acousto-optic Q-switch. Parameters (including transmittances at output mirror and crystal lengths) were optimized to obtain high output. Sub-milliwatt average power is predicted under current pump condition.